All-Fiber High Power Supercontinuum Generation by Cascaded Photonic Crystal Fibers Ranging From 370 nm to 2400 nm - Haoyu Zhang; Yue Li; Donglin Yan; Kegong Dong; Honghuan Lin; Jianjun Wang; Feng Jing (IEEE Photonics Journal, 2020)
104 W supercontinuum (SC) covering 370 nm-2400 nm is reported. High power visible SC is generated by pumping cascaded photonic crystal fibers (PCF) with 1064 nm picosecond pulse. Cascaded PCFs is fabricated by fusion splicing two different PCFs together with a coupling efficiency of 75%. For the purpose of avoiding fiber fuse phenomenon in PCF, the discharge time and intensity of fusion splicer should be precisely controlled. Two components of cascaded PCFs are pumped separately by 1064 nm picosecond pulse for comparing with the impact of cascaded PCFs. As a result of pumping cascaded PCFs, 104 W SC covering 370 nm−2400 nm is generated. Visible spectra (380 nm−780 nm) accounts for 50.4% (52.4 W) by numerical integration. To best of our knowledge, it's the first time that a visible SC with over a hundred watt output and 370 nm short-wave edge is obtained experimentally.